2016
DOI: 10.1515/rela-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Pre-fortis shortening in Czech English: A production and reaction-time study

Abstract: This study focuses on the production and perception of English words with a fortis vs. lenis obstruent in the syllable coda. The contrast is mostly cued by the duration of the preceding vowel, which is shorter before fortis than before lenis sounds in native speech. In the first experiment we analyzed the production of 10 Czech speakers of English and compared them to two native controls. The results showed that the Czech speakers did not sufficiently exploit duration to cue the identity of the word-fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
2
9
0
1
Order By: Relevance
“…In English, the contrast is not achieved through phonetic voicing but uses duration: the vowel will be significantly shorter before voiceless consonants (in dock) than before voiced ones (in dog). Not surprisingly, Skarnitzl and Šturm (2016) found that Czech speakers, who had a relatively strong accent in their English, did not exploit duration to cue this contrast.…”
Section: Consonants In Czech Englishmentioning
confidence: 91%
“…In English, the contrast is not achieved through phonetic voicing but uses duration: the vowel will be significantly shorter before voiceless consonants (in dock) than before voiced ones (in dog). Not surprisingly, Skarnitzl and Šturm (2016) found that Czech speakers, who had a relatively strong accent in their English, did not exploit duration to cue this contrast.…”
Section: Consonants In Czech Englishmentioning
confidence: 91%
“…Several studies were conducted on the acquisition of English final obstruent contrasts by speakers of Czech, another language without final voicing contrast. The results reported in Fejlová (2013) and in Skarnitzl & Šturm (2016) show that the Czech speakers did not sufficiently exploit duration to cue the identity of the word-final obstruent. The study by Skarnitzl and Šturm (2014) showed that the Czech subjects of their research tended to produce both the fortis and lenis obstruents without any phonetic voicing.…”
Section: Previous Research In Final Obstruent Acquisitionmentioning
confidence: 94%
“…Several specific pronunciation features can be identified as typical of Czech accent in English (Šimáčková and Podlipský 2012). The accent has its typical suprasegmental characteristics (Volín and Skarnitzl 2010), segmental features observable in connected speech (Šimáčková, Kolářová and Podlipský 2014), consonantal features (Skarnitzl and Šturm 2016) as well as vocalic features. Our learners' productions of English vowels, even at the relatively advanced levels of proficiency, continue to betray cross-linguistic influence of the small and relatively symmetrical Czech vocalic system, with vowel length distinctions in five long -short phoneme pairs /iːɪ, ɛːɛ, aːa, oːo, uː -u/.…”
Section: Efl Learners Who Used the English Vowel Trainer In The Current Studymentioning
confidence: 99%